Participatory impact assessment: Bridging the gap between scientists' theory and farmers' practice. (October 2016) - Schindler, Jana; Graef, Frieder; König, Hannes Jochen
Abstract: Food security is a major challenge for smallholders in Sub-Saharan Africa. Many development initiatives have attempted to enhance food security by improving agricultural production and productivity. An ex-ante impact assessment is a critical step for identifying positive and negative impacts before implementation of these agricultural innovations and it is therefore a critical component during project-/program planning. While many theoretical discourses have highlighted a strong need for active involvement of local stakeholders during project-/program planning to develop suitable solutions, in practice, local communities are still not mandatorily involved in the ex-ante impact assessment before the implementation of development initiatives. The purpose of this research is to highlight how stakeholders' and researchers' knowledge can enhance the quality of impact assessments if they are used in a complementary way. We applied two methodological impact assessment approaches (Framework for participatory impact assessment [FoPIA] and ScaIA-Food Security [ScaIA-FS]) to assess the impacts of five agricultural upgrading strategies (UPS) from a researcher's perspective as well as from a farmer's point of view in two case study villages in rural Dodoma, Tanzania. We observed that farmers and scientists had considerably different views on the impacts of the proposed agricultural UPS. While scientists focused on direct causal impact chains of the UPS, farmers considered more the indirect linkages, taking into account their complex livelihoods. Ex-ante impact assessment is a valuable tool to anticipate possible effects, and the process facilitates insights into complex socio-environmental contexts of local communities as well as structured thinking and knowledge exchange. We therefore see bi-lateral ex-ante impact assessments as a corrective step before UPS implementation, which would help to adapt solutions that will benefit local communities. Highlights: Ex-ante impact assessment supports to anticipate possible impacts of project interventions and makes them explicit Participatory impact assessment facilitates insights into the complex socio-environmental context of a local community Farmers and scientists have different views on the positive and negative impacts of proposed agricultural interventions Ex-ante impact assessment should be mandatorily applied at local community level during planning phase Ex-ante impact assessment is a critical step before implementation to adapt solutions to the context